Desenvolvimento e comportamento higiênico de Apis mellifera em colônias com rainhas selecionadas - Schafaschek, Tânia Patrícia (2014)
Three studies were conducted aiming at evaluating colonies of Apis mellifera honeybees formed by queens from different origins. It was verified the performance parameters, honey production, hygienic behavior, infestation by Varroa destructor on adult worker honeybees, varroa invasion rate in pupae of worker honeybees and total and effective reproduction of the varroa. It was evaluated selected queens for honey production and hygienic behavior and queens selected for royal jelly production from the program of honeybee selection from Universidade Estadual de Maringá (Maringá, state of Paraná, Brazil). These queens are selected based on genetic evaluation of matrices queens through evaluation of morphometric traits and queen weight at the emergence for honey production and also by evaluating the removal of dead brood in 24 hours by worker honeybees in daughters colonies of the matrices queens for hygienic behavior. The selection for royal jelly production was performed based on molecular markers for the expression of MRJP protein. Another evaluated group was with queens from queen breeder of Santa Terezinha, state of Santa Catarina, Brazil selected for hygienic behavior and monitored for V. destructor infestation. Unselected queens were also evaluated; they were randomly chosen in the apiary of Irineópolis, state of Santa Catarina and Mafra, state of Santa Catarina. In the first work was evaluated, in two experiments, the V. destructor infestation and the performance of A. mellifera colonies with queens selected for honey production, royal jelly production and also unselected queens, correlating with climatic variables. This trial I, in Campo Alegre, state of Santa Catarina, was performed using 10 Langstroth hives and in Mafra, state of Santa Catarina it was performed the trial II with 15 Schenk hives. Mapping in areas of sealed and unsealed brood, honey and pollen combs was performed at the introduction queen day and at 45 and 90 days after that. In trial I there was an interaction among the selection type of the queen and the evaluation period for areas of sealed brood, honey and total food. The selected group for royal jelly presented larger sealed brood area and smaller honey area at 90 days. The varroa infestation was lower (p<0.05) at 90 days. In the trial II there was no interaction among the evaluated parameters. The sealed brood area, the total brood and the total occupied area in the colony had effect of the type of queen selection and the evaluation period. The high relative humidity caused higher honey storage for the local group. In the second study it was evaluated the queen acceptance from different sources introduced in A. mellifera colonies already established in two seasons of the year. It was verified the winter survival, the colonies longevity and the influence of food supplementation. The queens from the breeding program at Universidade Estadual de Maringá (Maringá, state of Paraná), from a queen breeder of Santa Terezinha, state of Santa Catarina, and local queens (Irineópolis, state of Santa Catarina) were evaluated. There was effect of the origin and the season in which they were introduced (p<0.05) in queen acceptance. Queens from Maringa and Santa Terezinha had a higher probability of acceptance in April-Autumn. There was no interaction effect (p>0.05) between origin and food supplementation for the probability of surviving in the winter and in both season of queen introduction. The supplementation increased the probability of surviving in the winter (p<0.05) and a higher longevity of colonies with queens introduced in April. There was an interaction (p<0.05) of origin and food supplementation for longevity of colonies when the queens were introduced in December. In the third study, it was evaluated the hygienic behavior and variables related with V. destructor in colonies of A. mellifera with queens from different origins from October 2013 to June 2014. The group from Maringá had higher invasion rate and total reproduction of varroa, as the reduction of hygienic behavior occurred. This group presented reduction of effective reproduction, averaging of 2.3 fertile offspring. The average for hygienic behavior in this group was 84.0%. The group from Santa Terezinha, although less pronounced, had higher invasion rate from the reduction of hygienic behavior. The hygienic behavior remained stable, averaging 92.0%. For this group the total and effective reproduction was 1.72 and 0.95 individuals, respectively. Colonies with queen from Irineópolis t had the lowest hygienic behavior (78.0%) and the highest total reproduction (12.6) and effective (5.3). It was concluded that queens from different origins and selection processes presented different results in colony performance according to the environment in which they are settled and the food supplementation was primordial for colonies surviving in the winter and increased their longevity. The selection of queens reduced the varroa population, which is considered important to develop multifactorial studies, including hygienic behavior, mite reproduction reduction and its interactions with the selected traits to better understanding the population dynamics and resistance to this parasite colony .